Long-term mortality after community-acquired sepsis: a longitudinal population-based cohort study. Issue 1 (17th January 2014) - Wang, Henry E; Szychowski, Jeff M; Griffin, Russell; Safford, Monika M; Shapiro, Nathan I; Howard, George
Abstract : Objective: Prior studies have concentrated on the acute short-term outcomes of sepsis, with little focus on its long-term consequences. The objective of this study was to characterise long-term mortality following a sepsis event. Design: Population-based data from the 30 239 community-dwelling individuals in the REasons for Geographic and Racial Differences in Stroke (REGARDS) cohort. Setting: USA. Participants: Community-dwelling adults ≥45 years of age. Sepsis was defined as hospitalisation or emergency department treatment for a serious infection with the presence of ≥2 systemic inflammatory response syndrome criteria. Outcomes: 6-year all-cause mortality. The analysis utilised a time-varying Cox model adjusted for participant's age, demographic factors, health behaviours and chronic medical conditions. Results: The participants were observed for a median of 6.1 years (IQR 4.5–7.1). During this period, 975 individuals experienced a sepsis event. Sepsis hospital mortality was 8.9%. One-year, 2-year and 5-year all-cause mortality among individuals with sepsis were 23%, 28.8% and 43.8%, respectively, compared with death rates of 1%, 2.6% and 8.3% among those who never developed sepsis. On multivariable analysis, the association of sepsis with increased all-cause mortality persisted for up to 5 years, after adjustment for confounders; year 0.00–1.00, adjusted HR (aHR) 13.07 (95% CI 10.63 to 16.06); year 1.01–2.00 aHR 2.64 (1.85 to 3.77); year 2.01–3.00 aHR 2.18 (1.43 to 3.33); year 3.01–4.00 aHR 1.97 (1.19 to 3.25); year 4.01–5.00 aHR 2.08 (1.14 to 3.79); year 5.01+ aHR 1.41 (0.67 to 2.98). Conclusions: Individuals with sepsis exhibited increased rates of death for up to 5 years after the illness event, even after accounting for comorbidities. Sepsis is independently associated with increased risk of mortality well after hospital treatment.